Cold cathodes based on carbonic nanostructured layered structures - Belyanin, A. F.; Borisov, V. V.; Timofeev, M. A.; Lamskiy, A. N. (Technology and design in electronic equipment, 2013)
The paper describes formation conditions for and the structure of diamond-like materials films used in the manufacture of layered cold cathodes of emission electronics devices. The authors study the structure and field emission properties of layered structures with polycluster diamond and diamond-like carbon films (DCF) formed by various methods. It has been found that the best emission properties are characteristic of DCFs obtained by cathode sputtering. Emission from the surface of such films occurs on the boundaries of the globules.